Comparison of Clinical Efficacy and Safety Between da Vinci Robotic and Laparoscopic Intersphincteric Resection for Low Rectal Cancer: A Meta-Analysis - Zhang, Jie; Qi, Xingshun; Yi, Fangfang; Cao, Rongrong; Gao, Guangrong; Zhang, Cheng (Frontiers in Surgery, 2021)
Background and aims: The intersphincteric resection (ISR) is beneficial for saving patients’ anus to a large extent and restoring original bowel continuity. Laparoscopic ISR (L-ISR) has its drawbacks, such as two-dimensional images, low motion flexibility, and unstable lens. Recently, Da Vinci robotic ISR (R-ISR) is increasingly used worldwide. The purpose of this article is to compare the feasibility, safety, oncological outcomes, and clinical efficacy of R-ISR versus L-ISR for low rectal cancer. Methods: PubMed, EMBASE, Cochrane Library, and Web of Science were searched to identify comparative studies of R-ISR versus L-ISR. Demographic, clinical, and outcome data were extracted. Mean difference (MD) and odds ratios (OR) with their corresponding confidence intervals (CIs) were calculated. Results: Five studies were included. In total, 510 patients were included, of whom 273 underwent R-ISR and 237 L-ISR. Compared to L-ISR, R-ISR has significantly lower estimated intraoperative blood loss (MD=-23.31, 95%CI [-41.98, -4.64], P=0.01), longer operative time (MD=51.77, 95%CI [25.68, 77.86], P=0.0001), hospitalization days (MD=-1.52, 95%CI [-2.10, 0.94], P<0.00001), and postoperative urinary complications (OR=0.34, 95%CI [0.14, 0.80], P=0.01). Conclusions: The potential benefits of R-ISR as a safe and feasible alternative choice for the treatment of low rectal tumors.